Enhanced thermal performance and hydrochloric acid gas (HCl) emission mitigation in ammonium perchlorate (AP)-Based solid propellants with potassium permanganate (KMnO4)/AP dual oxidisers - Yaacob, Izzat Najmi; Gires, Ezanee; Basri, Adi Azrif; Ahmad, Kamarul Arifin; Kamal, Kamsani; Salleh, Nor Afizah; Shahedi, Suraya; Rasih, Fikri; Azizi, Zakwan; Dol, Sharul Sham; Mazlan, Norkhairunnisa (Elsevier Ltd, 2025)
The conventional propellant used in rocket boosters and tactical missiles commonly utilises ammonium perchlorate (AP). However, the release of harmful chloride fumes resulting from the combustion of AP during rocket launches contributes to a 1 % increase in air pollution. Generally, the perchlorate-based propellants contribute to pollution by hydrochloric acid (HCl), which can contaminate launch sites and potentially deplete the ozone layer. Several techniques have been employed to convert standard AP-based composite solid propellant (CSP) into green propellant. This study designed a minimum chlorine content propellant containing potassium permanganate, KMnO4/AP as a dual oxidiser and examined its properties in CSP formulation. This novel KMnO4/AP was characterised in terms of morphological structure, elemental analysis, and thermal decomposition properties by using scanning electron microscope (SEM), energy dispersive X-ray analysis (EDX), and differential scanning calorimetry (DSC) and thermogravimetry analysis (TGA), respectively. Additionally, heat of combustion analysis was examined through bomb calorimetry. The chlorine content investigations were experimentally carried out, and the results were compared with conventional AP-based CSP using gas bubbling and Mohr's titration method. From thermal decomposition analysis, sample KMnO4/AP (40:60) shifted high temperature decomposition (HTD) of AP to a lowest temperature of 331.32 °C with the highest heat release of 3721.2 J/g. Besides, sample KMnO4/AP (80:20) shows the highest reduction of chlorine concentration content with a reduction percentage of 58.25 %. Besides, KMnO4/AP (40:60) sample resulted in the highest value of heat of combustion with a value of 1254.01 cal/g. This study contributes to the development of environmentally friendly and sustainable oxidisers for solid rocket propellant applications.